Effect of Smell and Taste of Breast Milk and Sucrose on the Relief of Venipuncture Pain in Neonates: A Randomized Clinical Trail - Asieh Modaresi; Yadollah Zahedpasha; Seyedeh Roghayeh Jafarian_amiri; Mahmoud Haji Ahmadi; Roya Farhadi (Iranian Journal of Neonatology)
Background: Venipuncture is a common procedure in the neonatal department and causes significant pain for infants. This study aimed to compare the effect of tasting sucrose solution with those of smelling and tasting breast milk on the intensity of venipuncture pain in neonates. Methods: This clinical trial was performed on 99 full-term neonates at Bouali Sina Hospital in Sari, Iran. The subjects were randomly divided into three groups of 24% sucrose(n:34), breast milk smell (n:31) and breast milk taste(n:34). Their venipuncture pain was measured using neonatal infant acute pain assessment scale (NIAPAS). The vital signs of neonates were monitored from two minutes before to 60 seconds after venipuncture. The data was analyzed using the Shapiro-Wilks, Chi-square, Kruskal-Wallis, at a significant level of 5%, and the Friedman tests. Results: The mean scores of pain during venipuncture in the breast milk smell, breast milk taste, and sucrose groups were 7.22 ± 2.41, 8.58 ± 2.25, and 7.23 ± 2.61, respectively. The mean scores of pain 30 seconds after venipuncture in the breast milk smell and taste groups and the sucrose group were 2.25 ± 2.87, 4.41±4.30, and 2.70±3.18, respectively. The mean scores of pain 60 seconds after venipuncture in the breast milk smell and taste groups and the sucrose group were 0.45 ± 0.88, 1.55 ± 2.20, and 0.47 ± 0.96, respectively. The mean score of pain was significantly different at 30 and 60 seconds after venipuncture (P = 0.017 and 0.22, respectively). Conclusion: The smell and taste of maternal breast milk, in case of lack of sucrose, were effective in the relief of venipuncture pain among hospitalized neonates. It is suggested to use these non-invasive and cost-effective methods to relieve the pain of newborns during painful treatment procedures, especially when the mother is not present in the ward.